Your boss is an algorithm : artificial intelligence, platform work and labour - Aloisi, Antonio; De Stefano, Valerio (London [England] : Hart Publishing, 2022)
"What effect do robots, algorithms, and online platforms have on the world of work? Using case studies and examples from across the EU, the UK, and the US, this book provides a compass to navigate this technological transformation as well as the regulatory options available, and proposes a new map for the era of radical digital advancements. From platform work to the gig-economy and the impact of artificial intelligence, algorithmic management, and digital surveillance on workplaces, technology has overwhelming consequences for everyone's lives, reshaping the labour market and straining social institutions. Contrary to preliminary analyses forecasting the threat of human work obsolescence, the book demonstrates that digital tools are more likely to replace managerial roles and intensify organisational processes in workplaces, rather than opening the way for mass job displacement. Can flexibility and protection be reconciled so that legal frameworks uphold innovation? How can we address the pervasive power of AI-enabled monitoring? How likely is it that the gig-economy model will emerge as a new organisational paradigm across sectors? And what can social partners and political players do to adopt effective regulation? Technology is never neutral. It can and must be governed, to ensure that progress favours the many. Digital transformation can be an essential ally, from the warehouse to the office, but it must be tested in terms of social and political sustainability, not only through the lenses of economic convenience. Your Boss Is an Algorithm offers a guide to explore these new scenarios, their promises, and perils."--
Prologue -- 1. What Future for Work? -- 1. Keep Calm, the Reports of the 'End of Work' Are Greatly Exaggerated 1.1. The 'Robocalypse' Is Adjourned to a Later Date -- 2. Digital is Political: A New Mission for the 'Human in Command' -- 2. The Transformations of Work -- 1. The Consequences for the 'Work That Is Left' -- 2. Technology at Work 2.1. Robots and Industry: Intelligent Machines Enter the Factory 2.2. Remote Work: Home and Shop. Out of Hours and Out of Place 2.3. Selective Affinity: The Instant Matching of Supply and Demand -- 3. Work at the Service of Technology 3.1. 'People Are Numbers': Human Resources and Workforce Analytics 3.2. Your Boss Is an Algorithm 3.3. Not Everything That Is Intelligent Is Artificial -- 3. Rights in the Digital Age -- 1. What Do We Talk About When We Say 'Platform Work' (and Why Do We Talk About It So Much) -- 2. Doublespeak and the Spirit of Sharing: 'What Is Mine Is Yours' 2.1. Workers on Tap and Insatiable Appetites 2.2. Paradigmatic Platform: The Master-Server Dialectic 2.3. Brussels Calls to Say: Delivery Was Successful -- 3. Labour Regulation between Obsolescence and Resistance 3.1. A False Alternative between Protection and Flexibility 3.2. Towards a Universal Model of Protection for Modern Times? 3.3. The Big Family of Non-Standard Forms of Employment Conclusions: A Job Well Done -- 1. Social Law as a Future-Proof Toolkit 1.1. Universal Basic Income and the Sustainability of Radical Measures 1.2. Collective Autonomy vs Digital Despotism: Negotiating the Algorithm 1.3. And They Lived Happy and Connected: Saving the Digital Transformation from Itself
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Employees -- Effect of technological innovations on; Labor laws and legislation; Artificial intelligence -- Law and legislation; Electronic books